Effect of Tualang honey in acute kidney injury animal model - Hamad Mohamed, Zenab; Abdul Rahim, Roslina; Muhammad, Naznin; Abdullah, Nor Zamzila (Lap Lambert Academic Publishing, 2017)
BACKGROUND: Many researches have proven that there exists a complex association between progressive renal damage and hypercholesterolemia. However, there was little information about the early effect of hypercholesterolemia on the kidney. Additionally, although there is a growing insight into the causes and mechanisms of these diseases, preventive and therapeutic measures are still few. Hence, the aim of this study is to determine the acute and sub-acute effects of high cholesterol diet on the kidney, and to examine the protective role of tualang honey against these disease. METHODOLOGY: Fifteen female Sprague-Dawley rats were randomly divided into three groups: control group, fed with commercial rat pellet; high cholesterol diet group (HCD), fed with 12% cholesterol diet with 0.3% cholic acid, and HCD with tualang honey supplements at 1.4 g/kg/day orally group (HCD+TH). Biochemical analyses for lipid profile and renal function test were performed at completed 48 hours (day 3), day 7, and day 42 of the experiment. The rats were sacrificed at completed day 42 and the kidneys were harvested and subjected to histopathological examination. The data were analysed using ANOVA and LSD Post-Hoc test. RESULTS: Consumption of 12% cholesterol diet for six weeks resulted in an increment of the mean serum creatinine level of HCD and HCD+TH groups to 1.5 times the control level at the completed day 7. Also overall both the mean serum creatinine and blood urea levels were higher in HCD group than the control group. The mean TC showed an increasing trend throughout the experiment with the level being significantly higher than the control group at the completed day 42. A significantly higher mean serum LDL-c in the HCD group as compared to the control at the completed day 42 was also documented. The mean serum TG levels were higher than that of the control group at the completed 48 hours and day 7. The mean serum HDL-c showed a significant reduction in HCD group than the control group at the completed day 42. With tualang honey supplementation, the mean serum creatinine level showed significant reduction at 48 hours in the HCD+TH group as compared to the HCD group. There was also a reduction in the mean serum creatinine level at the completed day 42. As for the lipid profile, honey supplementation significantly reduced the mean TG and vLDL-c at the completed day 7 as compared to HCD group. Histopathologically the kidneys exhibited segmental mesangial hypercellularity and mesangial matrix expansion of almost all the glomeruli in both HCD and HCD+TH groups. CONCLUSION: The 12% cholesterol diet utilized in this study caused acute and sub-acute kidney injuries in the animal model while tualang honey at 1.4 g/kg/day orally exhibited lipid lowering activities and some degree of renoprotective effect against high cholesterol diet induced kidney injury.